Solution to the Homogeneous Boundary Value Problems of Free Vibrations of a Finite String - Dolya, P. G. (Журнал математичної фізики, аналізу, геометрії, 2008)
In the paper solutions to the homogeneous boundary value problems of free vibrations of a finite string are obtained in the d’Alembert form. The initial boundary value problems to vibrations of a string with free ends as well as with one end fixed and one free are solved.Mathematics Subject Classification: 35L05, 35C05.